Le CAP, portrait sociographique - Claire Lemêtre; Gilles Moreau (Cahiers de la Recherche sur l'Education et les Savoirs)
Now a hundred years old, CAP (Certificat d’aptitude professionnelle) is a vocational training certificate taken at secondary school in France. CAP may boast being one of the longest-standing diplomas in the French educational system, the fact remains that, since its creation, it has been subject to a number of fluctuations in terms of form, content and structure. Supported by a research work of statistical data collection, the present article gives an account of the extensive sociographical evolutions of this vocational certificate. Throughout this study, which does at times come up against the limits of incomplete statistical data, we are reminded of the heuristic virtues of a long-term sociographical research on such a subject.